Potensials Interior Design to Meet Cultural Needs Transformed by Covid-19 Pandemic by Interior Designer in Yogyakarta - M. Sholahuddin (Institut Seni Indonesia Yogyakarta, 2022)
This research aims to explore the perceptions of interior designers in Yogyakarta about the potential interior designs that would meet the cultural needs of “new normality” following the Covid-19 pandemic. The method used in this research was descriptive qualitative. The study found that interior designers in Yogyakarta believed that 1) the changes in design would involve the spatial, human, and technical aspects. Since pace is a fixed variable and humans are independent variables, interior designers would cre- ate new spaces and utilize present-day technology to maximize the technical aspects of their design. They would also give more consideration to the element of health. The interior designers also believed that 2) all projects in the future would apply the principles of the next normal and take health into serious consideration. The prin- ciples of the next normal interior design, namely human-centered design, historicity culture tradition, and interdisciplinary sustainability technology would be relevant to the cultural context following the Covid-19 pandemic. However, the pattern of hu- man behavior during the Covid-19 pandemic may be temporary, so further research is needed to examine whether this habit becomes everyone’s culture and whether it needs more detailed study to prepare for the establishment of new design standards. Potensi Desain Interior dalam Memenuhi Kebutuhan Budaya yang Ditransformasikan oleh Pandemi Covid-19. Penelitian ini bertujuan untuk menggali persepsi para desainer interior di Yogyakarta tentang potensi desain interior yang akan memenuhi kebutuhan budaya “kenormalan baru” pasca pandemi Covid-19. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Studi ini menemukan bahwa desainer interior di Yogyakarta percaya bahwa 1) perubahan desain akan melibatkan aspek spasial, manusia, dan teknis. Karena kecepatan adalah variabel tetap dan manusia adalah variabel independen, desainer interior akan menciptakan ruang baru dan memanfaatkan teknologi masa kini untuk memaksimalkan aspek teknis desain mereka. Mereka juga akan lebih mempertimbangkan unsur kesehatan. Desainer interior juga percaya bahwa 2) semua proyek di masa depan akan menerapkan prinsip-prinsip next normal dan mempertimbangkan aspek kesehatan dengan serius. Prinsip-prinsip desain interior next normal, yaitu human-centered design, historicity culture tradition, dan interdisciplinary sustainability technology akan relevan dengan konteks budaya pasca pandemi Covid-19. Namun, karena pola perilaku manusia selama pandemi Covid-19 mungkin bersifat sementara, diperlukan penelitian lebih lanjut untuk mengkaji apakah kebiasaan ini menjadi budaya setiap orang dan apakah perlu kajian lebih detail untuk mempersiapkan penyusunan standar desain baru.